'Hayi, they don't know Xhosa': Comparative isiXhosa teaching challenges in the Eastern Cape and Gauteng. Issue 3 (29th November 2019) - Kaschula, Russell H; Kretzer, Michael M
Abstract : Language-in-education policy in South Africa is underpinned by the Constitution. The gap that this research addresses is the inconsistency of policy implementation and the actual teaching of isiXhosa in primary schools. It analyses the official and overt language policy and the (covert) language practices at schools. Semi-structured interviews were conducted with language teachers and principals. Data were also gathered from classroom observations and document analysis in the Eastern Cape and Gauteng. On the one hand, there are standard language policy documents that exist. These advocate for English as a language of learning and teaching and isiXhosa as a subject. On the other hand, the daily reality in classrooms partly reflects this policy implementation. Furthermore, we conclude that there is no consistency in the teaching of isiXhosa home language, as well as First and Second Additional Language. There is insufficient teaching material and teachers are not capacitated in terms of pedagogical training in multilingual settings.